Usefulness ofdetermining exhaled nitric oxide levels for theassessment ofasthma severity inchildren - Anna Mierzejewska; Maria Jodłowska; Anna Kućko; Katarzyna Rybak; Malwina Sołtysiak; Sylwia Sroka; Bolesław Kalicki (Pediatria i Medycyna Rodzinna, 2015)
Asthma is a common disease, occurring increasingly among both children and adults. It is defined as a chronic inflammatory disease, characterized by hyperresponsiveness and reversible bronchial obstruction. The diagnosis of asthma in children is currently based mainly on clinical and spirometric evaluation as well as on the assessment of response to anti-inflammatory treatment. Currently there are ongoing discussions on the choice of optimal diagnostic and staging methods. Therefore, the measurement of the levels of exhaled nitric oxide (FeNO) is being seen as a viable option. The results of the measurement are obtained easily and non-invasively. High variability in the levels depending on both environmental factors and patient cooperation is a disadvantage of the test. The aim of this study was to determine the relationship between the levels of exhaled nitric oxide and the severity of asthma based on spirometric outcomes. A total of 141 children aged 5–17 years, including 35 patients diagnosed with asthma, among whom eight were in the stage of exacerbation, were qualified for the study. The control group consisted of 106 children admitted to the hospital for other reasons, with the exception of respiratory diseases. Spirometry and FeNO measurements were performed. No statistically significant differences were found between FeNO levels in patients with asthma or asthma exacerbations and the control group. The highest variation of FeNO levels was observed in the control group, indicating intersubject and factor variability of FeNO levels in exhaled gases. Although the utility of FeNO levels as an indicator of the severity of airway inflammation has been demonstrated in numerous studies, this study questions the usefulness of this parameter as a marker of asthma severity. This is probably due to the large intersubject variations in the concentration of exhaled NO, depending on patient cooperation and clinical status (and thus the accuracy of spirometry) and the fact that FeNO is affected by multiple other factors, such as diet rich in nitrogen compounds, hyperventilation, viral infections, tobacco smoke, airway pH. Only some of these factors can be eliminated, which renders the interpretation of FeNO concentration much more difficult and almost excludes its use in the diagnostics and monitoring of asthma on a large scale.